The impact of inspirational leadership on enhancing organizational culture at the Ministry of National Economy - Abu Jarbou, Yousef Ali (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the level of inspirational leadership and organizational culture among employees of the Ministry of National Economy and to reveal the relationship between inspirational leadership and organizational culture among employees of the Ministry of National Economy, and to identify the predictability of inspirational leadership in the light of enhancing organizational culture among employees of the Ministry of National Economy due to the variable (sex) And the study sample consisted of (281) workers in the Ministry of National Economy, and the researcher used the descriptive analytical approach, The results of the study indicated that the percentage of self- confidence, which reached (86.86%), which is a “very large” level, and the results of the study indicated that the percentage of future vision reached (85.64%), which is a “very large” level. The results of the study indicated that the percentage of workers’ empowerment reached (79.3%). It is a "significant" level, and the results of the study indicated that the percentage of the organizational culture level reached (79.96%), which is a significant level.
Keywords: inspirational leadership; organizational culture; Ministry of National Economy